1993
DOI: 10.2165/00002018-199309050-00006
|View full text |Cite
|
Sign up to set email alerts
|

A Risk-Benefit Appraisal of Injectable NSAIDs in the Management of Postoperative Pain

Abstract: The inadequacy of pain treatment has been demonstrated in many patient groups suffering from acute pain. The injectable nonsteroidal anti-inflammatory drugs (NSAIDs), including indomethacin, diclofenac, ketoprofen and ketorolac, provide relief from the pain associated with several different conditions. When administered alone or in combination with low doses of opioids, NSAIDs provide good pain relief after musculoskeletal trauma or operation. The main advantage of these agents is that they may form the first-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
2

Year Published

1995
1995
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 91 publications
1
33
0
2
Order By: Relevance
“…4 Previous investigators have reported no important gastrointestinal ulceration or hemorrhage with short-term (<48 hr) therapy. 3,4 Our results showed no deterioration in renal function following the use of NSAIDs. Clinical trials evaluating the effects of NSAID therapy on renal function in healthy patients have previously documented transient, but clinically insignificant increases in creatinine following NSAID use.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…4 Previous investigators have reported no important gastrointestinal ulceration or hemorrhage with short-term (<48 hr) therapy. 3,4 Our results showed no deterioration in renal function following the use of NSAIDs. Clinical trials evaluating the effects of NSAID therapy on renal function in healthy patients have previously documented transient, but clinically insignificant increases in creatinine following NSAID use.…”
Section: Discussionmentioning
confidence: 49%
“…3 Although the use of opioids can provide excellent analgesia, the doses necessary to provide effective pain relief may lead to undesirable side effects such as respiratory depression, sedation and nausea. 4 Non-steroidal anti-inflammatory drugs (NSAIDs) are potent analgesics 4,s but are inadequate for postoperative analgesia after major surgery when used alone. 3,5 However, NSAIDs in conjunction with opioids for postoperative analgesia have been shown to improve pain scores and reduce opioid consumption.…”
mentioning
confidence: 99%
“…Eighty two patients with stable intertrochanteric unilateral fracture were selected and divided into two groups: one received Methylprednisolone (MP) 125 mg and the other received placebo. Pain was evaluated at rest and 45° flexion of the hip in times 4,6,8,12,24,36, and 48 hours and during walking in times 24, 36, and 48 hours after the surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Pain control using NSAIDs and anticonvulsants has also been investigated in some studies, although their overdose may have such complications as GI bleeding or sedation [10][11][12]. Invasive ways of pain control also requires appropriate equipment and clinical conditions that suit the patient.…”
Section: Introductionmentioning
confidence: 99%
“…Although opioids are the traditional first-line treatment, 1 the potential adverse effects often make physicians reluctant to increase the dosage to achieve adequate analgesia. 2 Nonsteroidal anti inflammatory drugs (NSAIDs) provide effective analgesia for acute pain after minor and major surgery as a substitute for or as an adjunct to opioid analgesia and reduces opioid requirement during postoperative period. [3][4][5][6][7][8][9][10][11] The most recent parental non-steroidal antiinflammatory drug available for control of postoperative pain is ketorolac, a pyrolizine carboxylic acid derivative, structurally related to indomethacin.…”
Section: Introductionmentioning
confidence: 99%